Analisis kinerja keuangan pada PT. Bahana Security Indonesia Kota Makassar - Astuti, Andi Ria; Anwar, Anwar; Ruma, Zainal (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the financial performance of PT Bahana Security Indonesia by using the calculation of the ratio of profitability and activity. The type in this research is descriptive quantitative. So that the population in this study is data from the financial statements of PT Bahana Security Indonesia for the 2016-2020 period, with samples in the form of a statement of financial position (balance sheet) and profit and loss statements of PT Bahana Security Indonesia for the period 2016-2020. The data collection technique in this research is documentation. Meanwhile, the data analysis techniques used are Net Profit Margin (NPM), Total Asset Turnover (TATO), and Return On Investment (ROI). The results showed that the financial performance of PT. Bahana Security Indonesia for the 2016-2020 period is in the